Periovulatory neurohormone dynamics reveal an association between secretoneurin and GnRH across the mouse estrous cycle - Lu, Chunyu; Peng, Di; Smith, Kevin B.; Uju, Chinelo; Unniappan, Suraj; Duarte-Guterman, Paula; Ismail, Nafissa; Trudeau, Vance L. (Frontiers in Endocrinology, 2026)
IntroductionSurge release of luteinizing hormone (LH) from the pituitary is essential for fertility, as it triggers ovulation. Secretoneurin (SN), a conserved peptide derived from secretogranin-2, stimulates LH release, but its relationship to periovulatory changes in classical reproductive hormones remains unclear.MethodsWe measured fluctuations of two reproductive steroids and three peptides in the hypothalamus, pituitary, and ovary of female mice during the periovulatory period using a novel nano LC-MS/MS protocol. Immunohistochemistry for SN and GnRH was performed on brain samples. GT1-7 GnRH neuronal cells were exposed to various doses of SN and processed for PCR determination of Gnrh1 mRNA levels. A subset of these samples was subjected to RNA sequencing for pathway analysis.ResultsP4, E2, AVP, GnRH1, and SN varied across the cycle, whereas OXT was relatively stable. Ovarian P4 was highest at proestrus, while E2 peaked at diestrus. Hypothalamic P4 was elevated at diestrus, whereas pituitary P4 remained low and variable. AVP peaked at proestrus in both the hypothalamus and pituitary. SN levels were highest in the hypothalamus and pituitary at proestrus. GnRH1 increased in the hypothalamus and pituitary at proestrus but was undetectable in ovary. Regression analysis revealed a moderate positive association between hypothalamic SN and GnRH1. SN-immunoreactive fibers were found near GnRH neurons in the median and medial preoptic areas. In vitro, SN increased Gnrh1 mRNA in GT1-7 cells in a time- and dose-dependent manner. RNA sequencing after 6 h SN treatment highlights key signaling cascades including MAPK, transcriptional regulation, and calcium signaling pathways. Six upregulated TFs predicted to bind to the mouse Gnrh1 promoter were also linked to significant enrichment in ribosome-related processes, protein synthesis, and cellular component organization pathways.ConclusionThese findings identify a periovulatory association between SN and GnRH1 and provide a foundation for targeted studies needed to test causality in the mammalian reproductive neuroendocrine network.